Promotoras Legais Populares: avançando na luta pela igualdade de gênero e na compreensão da Educação de Jovens e Adultos - Santos, Raquel Auxiliadora dos (2014)
The Education of Youth and Adults (EJA) undergoes a process of paradigm change from a compensatory conception of basic education to lifelong learning. As a teaching modality, EJA needs to be understood in the broadest sense, connecting school experience with people s life and work expectations by seeking to contemplate their needs. The objective of this work is to describe and analyze one experience of EJA understood in the context of Lifelong Education: the Popular Legal Promoters Course (PLPs), which aims to train adult women to be multipliers of rights, laws and legal mechanisms in their communities. Women are still subordinate to hierarchies in different social contexts and struggle daily to uphold their rights. This research was carried out by conducting in-depth interviews with four PLPs graduated in the third group of the course in the city of Sao Carlos. Through content analysis and the Critical Communicative Methodology themes and categories were prepared highlighted in their transforming and exclusionary elements. Among the main elements of the PLPs course that contribute to EJA we have: practical utility of the content; the form of openly relation with knowledge; dialogical education; the importance of women's themes and feminism as well as multidisciplinary content. In this sense, the present dissertation focuses on the Popular Legal Promoters education as a Lifelong Education experience, which brings elements to the reformulation in the organization of EJA as a formative space that better suits women.